Water is Life, Progress to Secure Safe Water Provision in rRural Uganda Rugby - Fagan, Honor; Linnane, Suzanne; McGuigan, Kevin; Rugumayo, Albert (Practical Action Publishing., 2016)
A safe, adequate water supply within easy reach is still a dream for many people living in rural Africa. This book examines why such a basic service is not yet universally available by studying in detail one particular region of rural Uganda. What is the experience of women and children who have responsibility for fetching enough water for drinking, washing, cooking and feeding livestock? Are the village water committees run effectively? Is the policy and service delivery framework at national, regional and community level working to support borehole repair and maintenance? Can technical solutions such as SODIS and rooftop rainwater harvesting be both effective and gain local acceptance? Can GIS engage local people in gathering and using relevant data? Water is Life also studies the hydro-geological realities that present challenges to groundwater supply, and considers how climate change is likely to affect water supplies. The Water is Life: Amazzi Bulamu project is a five-year, interdisciplinary research collaboration between Irish and Ugandan higher education institutes and NGOs, centring on communities in the Makondo area of rural Uganda. By bringing together social, physical and environmental scientists to study these research questions, the project proposes solutions for community water supply that have eluded government initiatives and NGOs for decades. This book is important reading for researchers, students, and policy makers in NGOs and government departments with a responsibility for water supply.